Critical Consideration of Myxedema Coma in the Postoperative Setting: A Case Report. Issue 4 (15th February 2019) - Tran, Minh; Vincent, Lauren; Ho, Gordon; Kelly, Kaitlyn; Bouvet, Michael; Meier, Angela
Abstract : Myxedema coma is a rare but highly fatal condition with reported mortality >40%–50%. Early recognition and prompt treatment are critical for survival. Here we describe a case of possible postoperative myxedema coma after subacute neck hematoma evacuation after hemithyroidectomy in a patient on concurrent amiodarone therapy. Symptoms included somnolence, hypothermia, and prolonged QTc with torsades de pointes resistant to magnesium therapy requiring defibrillation and overdrive pacing. Consideration of the possible diagnosis of myxedema coma resulted in prompt therapy and symptom resolution within 48 hours. Thyroid disorders, although rare, should be considered in the postoperative setting.